Community-based weight loss programme targeting overweight Chinese adults with pre-diabetes: study protocol of a randomised controlled trial. Issue 4 (8th April 2020) - Ho, Mandy; Chau, Pui Hing; Yu, Esther Yee Tak; Ying, Michael Tin-cheung; Lam, Cindy Lo Kuen
Abstract : Introduction: Type 2 diabetes mellitus (T2DM) is one of the world's fastest growing health problems. Asians have a strong ethnic predisposition for T2DM, developing T2DM at a lower degree of obesity and at younger ages than other ethnic groups. T2DM has a gradual onset, with most individuals progressing through a pre-diabetic state, providing an opportunity to prevent T2DM and its complications. This study aims to evaluate the effectiveness of a community-based lifestyle intervention programme on weight loss and improvements in insulin sensitivity and cardiometabolic profiles in Chinese adults with pre-diabetes. Methods and analysis: This study is a 12-month, assessor-blinded randomised controlled trial. Adults with pre-diabetes (aged 40–64 years, n=180) with pre-diabetes are randomised into either an intervention group (receiving group-based lifestyle interventions) or a control group (receiving text messages containing health information). The intervention programme targets a weight loss of 5% during the first 6 months by restricting caloric intake and increasing physical activity. Participants in the intervention group will attend six group sessions and two individual face-to-face diet counselling sessions during the first 6 months, followed by monthly telephone support during the 6-month maintenance phase. Participants in the control group will receive monthly text messages containing general health information only. The primary outcome is weight loss (%). Secondary outcomes include insulin sensitivity (assessed using fasting insulin level and homeostatic model assessment of insulin resistance), glycaemic control (assessed using glycated haemoglobin level), lipid profile, blood pressure, carotid artery thickness, dietary intake and level of physical activity. Intention-to-treat analysis will be conducted using a generalised linear mixed effects model with a logit link and linear mixed models. Ethics and dissemination: This study has been approved by the relevant research ethics committee. The results will be disseminated through peer-reviewed journals and scientific presentations. Trial registration number: NCT03609697 .